An Integrated Model of Scenario Planning and Decision Tree Analysis for New Product Development Financial Planning: A Case of Smart Phone Development Project in Taiwan - Wu, Jei-Zheng; Lin, Kuo-Sheng; Wu, Chiao-Ying (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Demands of smart phones have been rapidly and dramatically increasing whereas R&D and marketing of smart phones have been facing severer competition and more dynamic environment. Most existing studies of new product development (NPD) focused on the traditional net-present-value (NPV) method and the real option analysis which are lack of flexibility to model asymmetric multi-stage decisions and flexible uncertain states. This study aims to integrate scenario planning and decision tree analysis for NPD evaluation. In so doing, scenarios for modeling uncertainties can be generated systematically. A case study of a Taiwanese OEM company shows the viability of the proposed model. Compared with the performance of the realized decisions, the proposed analysis is more robust and lowering the risk to minimal with appropriate R&D resource allocation. A two-way sensitivity analysis helps determine boundaries of the probability of R&D success and the cost of R&D where the R&D project will become profitable.